"PUPPETS" IN WOMEN'S ARTISTIC GYMNASTICS: THE COACH-GYMNAST RELATIONSHIP FROM PIERRE BOURDIEU'S LENS - Vítor Ricci Costa; Renato Francisco Rodrigues Marques; Mauricio dos Santos Oliveira; Myrian Nunomura (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
In Women's Artistic Gymnastics (WAG), athletes can be coach dependent, becoming submissive and this scenario may reflect subordination, harassment and abuse. This is worrying, because gymnasts are usually children. However, we  argue that coach conduct depends on complex interactions. Thus, we analyzed how the coach-gymnast relationship is built. We used Pierre Bourdieu's categories to argue our reflections. We identified that the domination forms in the coach-gymnast relationship are responsible for shaping long-lasting dispositions, triggered by a process marked by the inculcation and embodiment of certain practices. Thus, gymnasts develop a class habitus that reproduces and legitimates the logic of this field. Our appropriation of Bourdieu's lens has shown that the gymnasts are at a disadvantage in relation to the coaches and to the system. Therefore, these structures should not demand early outcomes, but allow gymnasts to decide whether they want to continue in this "game of domination".